Metabolic and reproductive state of Holstein cattle in the Carchi region, Ecuador - Balarezo, L. R.; García Díaz, J. R.; Hernández Barreto, M. A.; García López, R. (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the metabolic and reproductive state of dairy Holstein herds and the main factors affecting their reproductive indicators in Carchi province, Ecuador, a total 150 cows were selected. The main biochemical variables of 73 animals in the rainy season and 77 in the dry season were studied, the main indicators of reproductive efficiency and their relation with the metabolic state were also studied. Factors affecting reproductive indicators were determined by means of a multifactorial analysis of variance, using the Bonferroni test to compare the means. In the rainy and dry season, increases in beta-hydroxybutyrate were diagnosed in 68.4 % and 71% of the samples in relation to critical limits and blood urea nitrogen in 30 % and 33 % of them, poor body condition in 56 % and 61% of the animals and low concentrations of albumin in 30 and 33 % and phosphorus in 63 and 64.3% of the samples in each period of the year. The 70% of the animals showed calcium deficiency in the dry season. Cows had in very bad condition the reproductive indicators and body condition influenced (P <0.001) at conception calving and intrapartum intervals and gestational services, as well as (P <0.01) at first-service calving and interestral intervals. The state of beta-hydroxybutyrate (P <0.01) and the threemonth period in which the artificial insemination (P <0.05) was performed were also influenced on these reproductive parameters. It is concluded that in the studied herds are deficiencies of energy, protein and phosphorus with poor reproductive performance, in which beta-hydroxybutyrate, body condition and the trimester of the year in which artificial insemination is performed are significantly influenced. Key words: deficiencies, dairy Holstein, body condition, metabolic profile, reproductive indicators, bovines.